Factors Influencing the Application of Accounting Conservatism in the Company - Rahayu, S; ., Kusmuriyanto; ., Kiswanto; Indra Gunawan, D (KnE Social Sciences, 2018)
The purpose of this research is to determine the effect of the leverage, litigation risk, financial distress, political cost and company growth on accounting conservatism. The population of this study are 144 manufacturing companies which is listed in the Indonesian Stock Exchange (BEI) for the periode 2013-2016. Data were selected by purposive sampling method obtained by 32 sample. The units of analysis sample are 128 unit analysis. The method of data collection is documentation in this research. Data sourced from Indonesian Capital Market Directory and Audit Financial Report. The method of data analysis is multiple regression analysis, using SPSS 21 program for windows. The result of shows leverage, litigation risk, financial distress and company growth have positive significant effect to accounting conservatism. While political cost does not effect on accounting conservatism. Based on the research result, it can be concluded that leverage, litgation risk, financial distress and company growth can improve the application of accounting conservatism within the company, while and political costs have no effect the accounting conservatisme in company. Keywords: Accounting Conservatism; Leverage; Litigation Risk; Financial Distress; Political Cost; Company Growth